2017
DOI: 10.1021/acschembio.7b00459
|View full text |Cite
|
Sign up to set email alerts
|

Redesigned Spider Peptide with Improved Antimicrobial and Anticancer Properties

Abstract: Gomesin, a disulfide-rich antimicrobial peptide produced by the Brazilian spider Acanthoscurria gomesiana, has been shown to be potent against Gram-negative bacteria and to possess selective anticancer properties against melanoma cells. In a recent study, a backbone cyclized analogue of gomesin was shown to be as active but more stable than its native form. In the current study, we were interested in improving the antimicrobial properties of the cyclic gomesin, understanding its selectivity toward melanoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 42 publications
1
75
1
Order By: Relevance
“…It has been demonstrated that venom of snakes, scorpions and spiders has strong antibacterial effects (6). Some studies have also shown that AMPs have anticancer effects (7,8). Peptides from arthropods are cationic and amphiphilic and do not contain cysteine residues (9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that venom of snakes, scorpions and spiders has strong antibacterial effects (6). Some studies have also shown that AMPs have anticancer effects (7,8). Peptides from arthropods are cationic and amphiphilic and do not contain cysteine residues (9).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other AMPs, Gm shows cytotoxic activity against a wide range of pathogens, including clinically-relevant Gram-positive and Gram-negative bacteria, fungi and yeast, as well as demonstrating anti-malarial [ 3 , 4 ], anti-cryptococcal [ 5 ], and anti- Leishmania activity [ 1 , 3 , 6 , 7 , 8 , 9 , 10 , 11 ]. Gm also has in-vivo anti-cancer activity in a mouse model of melanoma [ 12 ], and in-vitro activity against a number of other human cancers [ 3 , 9 , 12 , 13 , 14 , 15 , 16 , 17 ]. In addition, Gm shows cytotoxic and anti-proliferative activity against devil facial tumour disease [ 18 ], a “parasitic” form of cancer that threatens the extinction of the Tasmanian devil ( Sarcophilus harrisii ), a unique Australian animal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Gm shows cytotoxic and anti-proliferative activity against devil facial tumour disease [ 18 ], a “parasitic” form of cancer that threatens the extinction of the Tasmanian devil ( Sarcophilus harrisii ), a unique Australian animal. A number of studies have successfully used different types of chemical modifications, such as cyclisation and/or amino acid substitution, to increase the anti-microbial or anti-cancer properties of Gm [ 3 , 8 , 9 , 18 ]. This wide range of cytotoxic activity, combined with its high serum stability [ 3 , 6 , 8 , 9 ] and moderate levels of haemolysis [ 1 , 6 , 7 , 8 , 9 ], make Gm of interest for the development of therapeutics to treat microbial infections and cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations